Overview of Registered Clinical Trials on Manual Therapy: Possible Implications of Genetic Testing for Personalized Treatment - Pozsgai Miklos; Szabo Istvan; Nusser Nora; Varnai Reka; Sipeky Csilla (INT INST ANTICANCER RESEARCH, 2022)
Background/aim: Manual therapy (MT) is a frequently applied intervention offering individualized treatment in the clinic. In addition to the traditional approaches of MT, measuring molecular response to MT may offer better understanding of MT outcomes in order to provide specific personalized treatment. The aim of this study was to summarize MT-related registered clinical trials, as well as to search for any evidence on MT and genetics.
Patients and methods: A comprehensive search was conducted within the Clinical Trials database with predefined keywords mining for all types of MT-related clinical trials.
Results: From the 47 trials, 20 had results and 27 had no results. MT alleviated pain and improved function almost in all trials. One registered clinical trial had investigated molecular outcomes of MT.
Conclusion: MT is an effective and individualized treatment offering option in the management of several conditions. Interestingly, a clinical trial was found investigating molecular genetics and MT pinpointing an already existing link between genetics and MT. Therefore, further clinical trials may focus on genetics and MT for providing specific personalized treatment in future.